Women and the environment - Altman, Irwin 1930-; Churchman, Arza (Springer Science + Business Media, LLC, 1994)
As society changes - due to (among other factors) political upheaval, racial tension, economic stress, and the rise of cultural subgroups - the changing roles of women in the public and private sectors are uniquely challenged by constraints and public policies regarding the physical environments in which women live and work. Women and the Environment illuminates the complex, many-layered relationship between women and a wide range of different physical environments, such as homes, workplaces, neighborhoods, communities, cities, and various public settings. It studies all the significant environments of a woman's life cycle from childhood to late adulthood, addressing such vital subjects as the interplay between women of varying ages, races, economic classes, occupations, communities, educations, and family structures and environments; obstacles and opportunities regarding women's roles in community action and public policymaking; legal and legislative barriers to environmental change, highlighted by successful case examples of women creating positive social change; and the philosophy of design and research issues involving women and environments. Women and the Environment will serve as an invaluable reference for researchers, professionals, and students in environmental psychology, personality and social psychology, gender studies, human ecology, and environmental design and planning.
Keywords: Femmes - Psychologie; Mulher e feminismo; Omgeving; Psicologia ambiental; Psychologie de l'environnement; Ruimte (algemeen); Vrouwen; Frau; Environment; Environmental psychology; Women -- Psychology; Women -- psychology; Psychologie; Umwelt; Aufsatzsammlung